N-(p-Tolylsulfonyl)-L-asparagine - Arshad, M.N.; Mubashar-ur-Rehman, H.; Khan, I.U.; Shafiq, M.; Lo, K.M. (International Union of Crystallography, 2010)
In the title compound, C11H14N2O5S, the amide O atom acts as a hydrogen-bond acceptor from a carboxylate O atom and a secondary amino N atom. In addition, one of the sulfonyl O atoms and the carbonyl O atom of the carboxyl group also form hydrogen bonds with the primary amido N atom. These intermolecular hydrogen-bonding interactions give rise to a layer structure, with the layers parallel to the ac plane.